Boosting propane dehydroaromatization by confining PtZn alloy nanoparticles within H-ZSM-5 crystals. Issue 24 (31st August 2022) - Chen, Hui; Li, Wei; Zhang, Mingchao; Wang, Wangyang; Zhang, Xian-Hua; Lu, Fa; Cheng, Kang; Zhang, Qinghong; Wang, Ye
Abstract : A Pt–Zn@H-ZSM-5 catalyst with Pt–Zn alloy nanoparticles confined in H-ZSM-5 crystals exhibits a significantly improved performance in the propane dehydroaromatization reaction. Abstract : Propane dehydroaromatization (PDA) to high value-added aromatic hydrocarbons, such as benzene, toluene, and xylene (BTX), is an attractive but challenging process. The traditional Zn/H-ZSM-5 or Ga/H-ZSM-5 catalysts can offer considerable PDA performances but still suffer from low activity and poor stability because of harsh reaction conditions. Here, we report a multifunctional Pt–Zn@H-ZSM-5 catalyst that exhibits a significantly improved performance in the PDA reaction at 550 °C, with a single-pass propane conversion of 74%, aromatics selectivity of 56%, and CH4 selectivity of only 4.7%. The yield of aromatics is twice as much as those of Zn/H-ZSM-5 and Ga/H-ZSM-5 catalysts. We have demonstrated that the Pt–Zn alloy nanoparticles with an average size of 2.4 nm are uniformly confined within H-ZSM-5 crystals, providing atomic-scale proximity between metal and zeolite acid sites. This unique structure enhances not only the dehydrogenation of the propane feedstock in the initial reaction stage but also the dehydrogenation of cyclic C6+ hydrocarbons by the recombinative desorption of surface hydrogen species in the last stage while suppressing the side hydrogenolysis and hydrogen-transfer reactions. Furthermore, the Si/Al ratio of H-ZSM-5, the synergistic effect between platinum and zinc, and the location of Pt–Zn nanoparticles over composite catalysts have also been discussed. These findings suggest that via bimetallic alloying and rational arrangements of functional sites at the nanoscale, the multistep PDA reaction can be greatly intensified.